Desain Unified Modeling Language (UML) Dalam Perancangan Aplikasi Hauling Trip di Industri Tambang Batubara - Ronal Sinambela (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Mining is a strategic industry sector in Indonesia, so many entrepreneurs who take opportunities in the mining industry and other industries that support the mining industry. The business process that the authors propose is part of the industry that supports the mining industry. The authors believe that the proposal has a market in need, because it can increase the effectiveness and efficiency of the process of hauling trip that can later support the income for the coal mining company. The process is by designing the Unified Modeling Language (UML) design and describing the application interface to model the data management system in the process of hauling trip. Through application hauling trip system that authors give believed to be more effective and efficient in supporting the company's income. This can be explained through the accuracy and speed of coal delivery (hauling trip), eliminating the use of paper, reducing the number of employees (allocation of employees) and facilitate the user in data processing. UML method is very helpful in the process of designing a data management system for hauling trip, this application can be used as data management Sara, especially for coal mining companies.